2015
DOI: 10.1371/journal.pone.0144546
|View full text |Cite
|
Sign up to set email alerts
|

NGS Transcriptomes and Enzyme Inhibitors Unravel Complexity of Picrosides Biosynthesis in Picrorhiza kurroa Royle ex. Benth

Abstract: Picrorhiza kurroa is an important medicinal herb valued for iridoid glycosides, Picroside-I (P-I) and Picroside-II (P-II), which have several pharmacological activities. Genetic interventions for developing a picroside production platform would require knowledge on biosynthetic pathway and key control points, which does not exist as of today. The current study reports that geranyl pyrophosphate (GPP) moiety is mainly contributed by the non-mevalonate (MEP) route, which is further modified to P-I and P-II throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 64 publications
3
34
0
Order By: Relevance
“…Based on precursor feeding experiments, researchers established the pathway of catalpol biosynthesis and inferred that catalpol and other iridoid glycosides were generated from geraniol, which was produced through a combined biosynthetic route involving non-mevalonate (MEP) and mevalonate (MVA) pathways [19,20]. Shitiz et al reported that the complete biosynthetic pathway of catalpol has been deciphered for all possible intermediates with their corresponding enzymes in Picrorhiza kurroa (Figure 6A) [21]. The putative genes encoding enzymes in the upstream of the iridoid pathway, including geraniol synthase (GES), geraniol 10-hydroxylase (G10H), cytochrome P450 reductase (CPR), and 10-hydroxygeraniol oxidoreductase (10HGO), have been identified in R. glutinosa [16].…”
Section: Resultsmentioning
confidence: 99%
“…Based on precursor feeding experiments, researchers established the pathway of catalpol biosynthesis and inferred that catalpol and other iridoid glycosides were generated from geraniol, which was produced through a combined biosynthetic route involving non-mevalonate (MEP) and mevalonate (MVA) pathways [19,20]. Shitiz et al reported that the complete biosynthetic pathway of catalpol has been deciphered for all possible intermediates with their corresponding enzymes in Picrorhiza kurroa (Figure 6A) [21]. The putative genes encoding enzymes in the upstream of the iridoid pathway, including geraniol synthase (GES), geraniol 10-hydroxylase (G10H), cytochrome P450 reductase (CPR), and 10-hydroxygeraniol oxidoreductase (10HGO), have been identified in R. glutinosa [16].…”
Section: Resultsmentioning
confidence: 99%
“…In Salvia miltiorrhiza , it has been reported that MVA pathway flux plays main role in cell growth, whereas the intermediates of MEP pathway are the major source of tanshinone biosynthesis [20]. Similarly, in Picrorhiza kurroa the role of the MEP pathway in picroside biosynthesis was determined by using enzyme inhibitors mevinolin and fosmidomycin along with aminooxy acetic acid, glyphosate and actinomycin D [31]. In N. nimmoniana camptothecin production involves a complex network of pathways including MEP, MVA, shikimate and seco-iridoid pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MEP has been reported as a major route for production of seco-iridoid moiety secologanin in C. roseus [29] and taxol in Taxus baccata [30]. Similarly, in Picrorhiza kurroa , by using different enzyme inhibitors (fosmidomycin, mevinolin, glyphosate and aminooxy acetic acid) and transcriptional inhibitor actinomycin D, confirmed that non-mevalonate pathway is the main source of picroside biosynthesis [31]. In Arabidopsis , transient reduction of sterol levels were observed in presence of HMGR inhibitor (lovastatin), indicating that the plastidial MEP pathway compensates for the lack of cytosolic IPP required for synthesis of cytosolic sterols [32].…”
Section: Introductionmentioning
confidence: 92%
“…The biosynthesis of P-I proceeds via non-mevalonate (MEP), mevalonate (MVA), shikimate/phenylpropanoid and iridoid pathways 5 . During the past years, numerous efforts have been carried out to shortlist candidate genes involved in P-I production through gene expression analyses performed under differential conditions of picrosides accumulation in P. kurroa 6 7 8 9 10 11 12 . Despite interesting cues obtained from these reports, no information is yet available on what mechanism controls the flux of P-I biosynthesis in P. kurroa .…”
mentioning
confidence: 99%